Lessons learned on scaling Aflasafe® through commercialization in Sub-Saharan Africa - Konlambigue, Matieyedou; Ortega-Beltran, Alejandro; Bandyopadhyay, Ranajit; Shanks, Tracy; Landreth, Edward; Jacob, Oscar (International Food Policy Research Institute, 2020)
Aflatoxin contamination of several crops is common in tropical and subtropical regions. Maize and groundnut, staples for billions of people, are among the most susceptible to contamination, primarily caused by the fungus Aspergillus flavus. Globally, an estimated 25 percent of aflatoxin-prone crops are contaminated with aflatoxins and/or other mycotoxins. Depending on the dose and exposure period, these toxins can cause severe health detriments in humans and animals. Farmers producing contaminated crops cannot sell to premium markets, including export markets.